Satuan Pengawasan Internal : Harapan dan Realita - Fitri, Sri Adella; Eficandra; Rahmi, Mega; Sulastri Caniago; Yosep Eka Putra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the role of internal control at PTKIN X in West Sumatra. Thework environment at PTKIN X in West Sumatra can cause differences in mindsets,perspectives, values that are believed to be, and the way a person does work. This willcertainly result in the supervision carried out, whether the implementation of supervisionis as expected, or vice versa. The type of research conducted is field research using asurvey approach. Researchers dig up information through in-depth interviews of therespondents (in-depth interviews). The results obtained from the supervision have beencarried out in various stages, starting from socialization to the overall implementationstage. Supervision is carried out by combining the pattern of Preventive audit with postaudit. The implementation of supervision at PTKIN X is carried out with the support of theleadership in various aspects, ranging from completeness, completeness of facilities andinfrastructure, maximum human resource development and flexibility in the developmentof supervision programs. The Internal Supervision Unit will become a functioning organwhen all elements have understood the meaning of the existence of supervision, withoutany supervision over the duties and functions of the Internal Audit Unit.